Importance of sonographic paratracheal lymph node evaluation in early autoimmune thyroiditis - Örmeci, Tuğrul; Çolakoğulları, Mukaddes; Orhan, İsrafil; Şakul, Bayram Ufuk (Tubitak Scientific, 2016)
Background/aim: To review the sonographic views of paratracheal lymph nodes (PLNs) in the diagnosis and during different stages of autoimmune thyroiditis. Materials and methods: Features of the PLNs (left and right), thyroid sonography, and laboratory data were investigated in 126 cases. Patients were divided into three groups by using thyroid sonographic criteria in the literature (group 1: control, group 2: early-stage/ indeterminate, group 3: definite thyroiditis). Indeterminate patients were followed up for 1 year and included as indeterminate/earlystage thyroiditis patients. Results: Percentage of right and left PLN was 13.3% and 46.2% in control cases, 21.2% and 80% in early-stage/indeterminate cases, and 41.3% and 88.5% in definite thyroiditis cases. Significant among-group differences were evident in terms of right and left PLNs presence (Pearson chi-squared test, P = 0.011 and P = 0.001). Conclusion: Careful and thorough review of the PLNs can ensure diagnosis of autoimmune thyroiditis even in cases of early stage of the disease and prevent false-negative diagnoses.
Keywords: Autoimmune Thyroiditis; Paratracheal Lymph Nodes; Thyroid; Ultrasound